Analysis and Implementation of the PCQ Method in MikroTik-Based Bandwidth Management - Anton; Corleon Adonay Theofilus; Hendra Supendar; Hilda Amalia; Salman Alfarizi; Mochamad Wahyudi; Lise Pujiastuti (LPPM Universitas Bina Sarana Informatika, 2026)
This study aims to implement bandwidth management using the Per Connection Queue (PCQ) method on a MikroTik router to overcome uneven bandwidth distribution. The main problem frequently encountered is the lack of optimal network traffic management, which impacts network performance and work productivity. The research method used is the Network Development Life Cycle (NDLC) with data collection techniques through observation, interviews, and literature studies. The analysis results indicate that the network does not yet have a bandwidth management system and priority allocation among departments. The proposed solution is the implementation of Simple Queue combined with the PCQ method to distribute bandwidth fairly according to the needs of each floor or department. The testing results show that the PCQ method can distribute bandwidth more systematically and stably, with achieved bandwidth values close to the predetermined targets, such as the 17th floor achieving 68.97/69.53 Mbps from a target of 70 Mbps. The study concludes that the combination of Simple Queue and PCQ on a MikroTik router is effective in creating fair, measurable, and efficient bandwidth management that supports business activities.